2018
DOI: 10.1007/s10439-018-2065-z
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Layer Vascular Grafts Fabricated by Combined E-Jet 3D Printing and Electrospinning

Abstract: Small-diameter tissue-engineered vascular grafts are urgently needed for clinic arterial substitute. To simulate the structures and functions of natural blood vessels, we designed a novel triple-layer poly(ε-caprolactone) (PCL) fibrous vascular graft by combining E-jet 3D printing and electrospinning techniques. The resultant vascular graft consisted of an interior layer comprising 3D-printed highly aligned strong fibers, a middle layer made by electrospun densely fibers, and an exterior structure composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 29 publications
0
54
0
Order By: Relevance
“…The longitudinally aligned fibers significantly promoted ECs proliferation and migration, and good cell infiltration was observed in the exterior layer (Huang et al, 2018). At first, the effect of porosity and pore size was demonstrated to be a critical factor which was associated with cell infiltration.…”
Section: Strategies For Ecm and Smcs Regenerationmentioning
confidence: 97%
See 4 more Smart Citations
“…The longitudinally aligned fibers significantly promoted ECs proliferation and migration, and good cell infiltration was observed in the exterior layer (Huang et al, 2018). At first, the effect of porosity and pore size was demonstrated to be a critical factor which was associated with cell infiltration.…”
Section: Strategies For Ecm and Smcs Regenerationmentioning
confidence: 97%
“…Researchers have made great strides in the development of constructs at the nanoscale that interact with cells and cause blood vessel formation. Previous studies found that the ECM compositions and topography have an influence on the function of ECs (Kumbar, James, Nukavarapu, & Laurencin, 2008;Peran et al, 2012;Viswanathan et al, 2015;Wilgus, 2012 longitudinally-aligned strong PCL fibers, which afforded the graft the essential mechanical support and promoted the growing, spreading, and migration of ECs (Huang et al, 2018).…”
Section: Surface Topography Modificationmentioning
confidence: 99%
See 3 more Smart Citations